2021
DOI: 10.3390/jcm10214934
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Perineal Tear Peripartum after Two Antepartum Perineal Massage Techniques: A Non-Randomised Controlled Trial

Abstract: Perineal massage increases elasticity of myofascial perineal tissue and decreases the burning and perineal pain during labour, thus optimising child birth, although an application protocol has not been standardised yet. The objective of this study is to determine the efficiency of massage in perineal tear prevention and identification of possible differences in massage application. Total of 90 pregnant participants were divided into three groups: perineal massage and EPI-NO® device group, applied by an expert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
(38 reference statements)
0
4
0
6
Order By: Relevance
“…As other authors show us, perineal tears are primarily found in young women, and these women are often primiparous. The author Álvarez-González M et al, shows us in her experimental study on perineal trauma that young women in their thirties are the most affected and vulnerable to perineal tears with a very high frequency [ 15 ]. The high prevalence of tears in our region shows good monitoring of young women during childbirth and the implementation of preventive measures to protect the perineum.…”
Section: Discussionmentioning
confidence: 99%
“…As other authors show us, perineal tears are primarily found in young women, and these women are often primiparous. The author Álvarez-González M et al, shows us in her experimental study on perineal trauma that young women in their thirties are the most affected and vulnerable to perineal tears with a very high frequency [ 15 ]. The high prevalence of tears in our region shows good monitoring of young women during childbirth and the implementation of preventive measures to protect the perineum.…”
Section: Discussionmentioning
confidence: 99%
“…The intervention protocol has been used previously [ 16 ]. The procedure included direct manual techniques, the use of the EPI-NO ® device (Northampton, UK), and another external manual technique [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Pada kasus ruptur perineum seringkali di dapatkan trauma di beberapa bagian seperti pada serviks, vagina, dan vulva termasuk daerah labial, periclitoral, dan periurethral serta yang paling sering pada daerah perineum. Selama persalinan sebagian besar ruptur perineum paling sering terjadi di sepanjang dinding posterior vagina dan memanjang hingga ke anus (1)(2)(3) Ruptur perineum dapat diklasifikasikan menjadi empat derajat berdasarkan tingkat keparahannya. Derajat pertama hanya mempengaruhi bagian mukosa vagina atau kulit perineum;derajat kedua mempengaruhi daerah serat otot perineum;derajat ketiga,lesi otot perineum mempengaruhi otot sfingter anal; sedangkan pada ruptur perineum derajat ke empat, mengenai mukosa dimulai dari epitel vagina hingga epitel anal (4) Ruptur perineum merupakan salah satu penyebab tertinggi kedua perdarahan ibu postpartum.…”
Section: Pendahuluanunclassified